تأثير أسلوب التعلم فكر-تكلم-اكتب ومنظور بيئة تعلم اللغة العربية في مهارة الكتابة في الصف الحادي عشر باالمدرسة الثانوية الإسلامية أبدية فاطي للسنة دراسية 2023-2024 - Al'arif, Irza Maulana; Alfurochmatin, Anisa (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
The aim of this research is to determine the effect of the learning style Think Talk Write (TTW) and the perspective of the Arabic language learning environment on learning Arabic in writing skill in the eleventh grade at the Islamic High School Abadiyeh Fati for the academic year 2023-2024. The background of this research is because the researcher observed the school and had the idea of ​​providing a new incentive in the form of the learning style Think Talk Write (TTW). This research uses the quantitative method where the focus is on testing whether there is an effect of the independent variable on the dependent variable. There are two independent variables here, namely the learning style TTW and the perspective of the language environment. Testing the learning style TTW uses a kovarian analysis test, that is, to see if there is an effect on the writing skill. At the same time, to analyze the perspective of the language environment using a questionnaire. The conclusion of this study is that there is a significant influence of the Think-Talk-Write (TTW) learning method and the language environment on Maharah Kitabah (writing skills). The results of the analysis show that the TTW learning method has an influence of 58.6%, while the language environment has a greater influence, namely 85%.